Sodobno irsko gledališče in digitalna kulturna - Butler, Angela (Amfiteater (Ljubljana), 2017)
This article will explore the question of how contemporary Irish theatre navigates and responds to digital culture and emergent counter-attention modes. More particularly, how does Irish theatre appeal, interrogate, and exploit the strategies used by new communication technologies in order to appeal to a contemporary Irish theatre audience? I will begin to tease out this enquiry by examining a number of performances programmed as part of the 2015 and 2016 Dublin Theatre Festival, namely Dead Centre's Chekhov's First Play, ANU Productions and CoisCéim's These Rooms, and Michael Keegan-Dolan's Swan Lake/Loch na hEala. These performances engage specifically on the effects of the digital culture shift in Ireland - a shift, I will argue, that has affected the ways contemporary Irish theatre audiences approach and experience certain types of performance. The article focuses on several performances from the Dublin Theatre Festival 2015 and 2016 programmes in order to explore the cultural shift in Ireland towards digital culture and how it has transformed the way contemporary Irish theatre is defined, created and consumed. Looking at specific programming choices for the 2015 and 2016 Dublin Theatre Festival, this article traces the pervasive nature of information-intensive environments in Ireland and links it to the bodily, immersive- and affective performances programmed as part of the Festival.
Keywords: afekt; affect; digital culture; digitalna kultura; gledališke predstave; Irish theatre; irsko gledališče